UtiUzation of nuclear poiyhedrosis virus in the integrated control of fruit-borer (Helicoverpa armlgera) on tomato (Lycopersicon esculentum) - POKHARKAR, D S; CHAUDHARY, S D; VERMA, S K (The Indian Journal of Agricultural Sciences, 2013)
An experiment was conducted during spring season of 1992 and 1993 to study the effectiveness of nuclearpolyhedrosis virus alone and in combination with endosulfan in the integrated control of fruit-borer [Helicoverpaarmigera (Hubner) on tomato (Lycopersicon escllientum Miller nom. cons.). Three sprays of endosulfan 0.07% at 10-dayintervals starting from 50% flowering of the crop proved to the best. Likewise application of Helicoverpa armigeranuclear polyhedrosis virus @ 700 larval equivalen/ha gave better protection to tomato crop from, H. armigera to98.25-100.00% reduction in larVal population, 6.89% mean fruit damage, 57.49 kg/plot (4 m X 5 m) mean total YIeldand 53.64 kg/plot mean marketable yield; and it was as effective as Helicoverpa almigera nuclear polyhedrosis virus@ 500 larvae equivalent/ha dose. Sequential application with first spray of endosulfan 0.07% followed by 2 sPraYs ofHelicoverpa armigera nuclear polyhedrosis virus @ 250 larval equivalentlha greatly reduced the larval popUlation and wascomparable with endosulfan 0.07% applied alone in 3 sprays.